Needs Analysis for the Development of Web-Based Interactive Learning Media Using Google Sites to Improve Learning Outcomes on Regular Straight Motion Material in Class XI in Bengkulu City High School - Puan Aisyah Maharani (Indonesian Journal of Pedagogy and Teacher Education, 2023)
The formulation of the problem of this study is whether it is necessary to analyze the development of web-based interactive learning media using google sites to improve learning outcomes on Regular Straight Motion material? The purpose of this study was to determine the analysis of the development of web-based interactive learning media using google sites to improve learning outcomes on the material of regular straight motion. The research method used in this research is descriptive qualitative, where literature studies, observations, interviews and questionnaires are used to collect data. The data analysis technique used was qualitative data analysis. SMA Negeri 1 Bengkulu City, SMA Negeri 3 Bengkulu City, and SMA Negeri 9 Bengkulu City are the research samples. The population taken is physics teachers and students of class X and XI IPA. This research was conducted from June to August 2023. Based on the results of observations, literature studies and data from interviews, students need interactive learning media such as google sites to help students improve learning outcomes. Therefore, it is necessary to analyze the development of interactive learning media using google sites that can help students improve physics learning outcomes and can play an active role and no longer have difficulty understanding physics learning.